An observational study of the efficacy of azithromycin in erythema annulare centrifugum. (3rd January 2018) - Sardana, K.; Chugh, S.; Mahajan, K.
Summary: Erythema annulare centrifugum (EAC) is a form of figurate erythema consequent to a cutaneous hypersensitivity reaction to an underlying agent. In the present study, we aimed to assess the role of oral azithromycin in cases of idiopathic EAC. We performed an open trial of azithromycin in 10 patients with idiopathic EAC. Histopathological examination of biopsies was performed to exclude any alternative diagnosis and to assess the depth of the infiltrate. Patients were administered oral azithromycin 250 mg once daily until clinical resolution of the disease, and followed up regularly to monitor for possible relapse. Histopathological examination of the 10 biopsies revealed superficial pattern in 3, deep pattern in 2 and mixed pattern in the remaining 5. Of the 10 patients, 8 responded to azithromycin 250 mg, with no relapse during follow‐up. Oral azithromycin might be a promising therapy in cases of idiopathic EAC. Cases with a superficial pattern respond earlier than cases with a deep pattern.